2017
DOI: 10.1177/1758834017724314
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib in metastatic renal cell carcinoma: latest findings and clinical potential

Abstract: Since the advent of immunotherapy revolutionized the treatment of metastatic renal cell carcinoma (mRCC), the attention of oncologists has been unavoidably shifted from tyrosine kinase inhibitors (TKIs) to immune checkpoint blockade, with the associated risk of listing cabozantinib as just one of many available TKIs. On the contrary, we think that cabozantinib represents a very good option for mRCC treatment, with outstanding outcomes in terms of response rate, progression-free survival, overall survival and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Interestingly, cabozantinib efficacy seems to be independent of MET expression and by its typical "VEGF inhibition-related" toxicity profile. These previous data, together with our current findings, suggest that maintaining "VEGF pressure" can still slow disease progression irrespective of the primary sensitivity to TKI [21]. Finally, we provided informative observations on pathological characterization: our population included a relatively high proportion of tumors with sarcomatoid features (18%) compared with historical cohorts [22,23], underlining the interest for different therapeutic strategies in these poorprognosis subtypes, which may benefit from conventional chemotherapy [24] and possibly from the use of CKIs [25].…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, cabozantinib efficacy seems to be independent of MET expression and by its typical "VEGF inhibition-related" toxicity profile. These previous data, together with our current findings, suggest that maintaining "VEGF pressure" can still slow disease progression irrespective of the primary sensitivity to TKI [21]. Finally, we provided informative observations on pathological characterization: our population included a relatively high proportion of tumors with sarcomatoid features (18%) compared with historical cohorts [22,23], underlining the interest for different therapeutic strategies in these poorprognosis subtypes, which may benefit from conventional chemotherapy [24] and possibly from the use of CKIs [25].…”
Section: Discussionsupporting
confidence: 85%
“…TKI including Axitinib, Sorafenib, Sunitinib, Pazopanib, and Tivozanib inhibit VEGF signaling by targeting the intracellular domain of the VEGFR; however, mTOR–raptor signaling is a potential target for antitumor therapy and mTOR inhibitors are currently under investigation for the treatment of various human cancers [ 44 ]. Cabozantinib represents a very good option for mRCC treatment, with outstanding outcomes in terms of response rate, PFS, OS, and quick time to treatment response [ 45 ]. Everolimus is an orally active mTOR inhibitor, and VEGF is a potent proangiogenic protein that plays an important role in tumor angiogenesis [ 10 ] and acts by binding to the VEGFR on endothelial cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cabozantinib is another TKI that targets multiple receptors, including c-MET, VEGF, RET, KIT, AXL, TIE2, and FLT3 [43]. Data from phase I study from Choueiri et al demonstrated safety and tolerability in RCC [44].…”
Section: Tkis Targeting Metmentioning
confidence: 99%